Protagonist of Tamil females in processing and marketing of dry fish in coastal villages of Jaffna, Sri Lanka - Shivany, S. (Trans Stellar Journal Publications, 2019)
Silent contribution of the outstanding performance of Tamil Female still face pressure in their path towards their life development, which make them a cry vibrate in North Sri Lanka. Tamil female continuously contribute largely for the different sector of development of the country. Dry fish sector significantly contributes to the agriculture sector, which earns notable contributions of foreign income. Traditionally Tamil female underwrite to fishers sector, but their protagonists in dry fish processing and marketing is important because there are the processers and marketers in the local markets. Even though their contribution is very large extent, lack of identification of their protagonist in their coastal villages. Due to the 30 years of prolonged war many fishing community have changes their livelihoods, and their protagonists have been transformed. Women in fishing sector especially in coastal villages rarely observed by the academic researchers, and the silent contribution of Tamil towards dry fish sector in coastal villages of Jaffna district was not considered as imperative. Present study combined both the qualitative and quantitative methods to collect data. Data were collected from Tamil women who involved in fish processing and marketing of dry fishes in twelve fishing villages such as Madagal, Kankesanthurai, Palali, Myliddy, Thondamanaru, Velvettiturai, Point Pedro, Passaiyoor, Karainagar, Mandathivu, Navanturai and Velanai. Findings show that majority of Tamil female are poor. Fish gutting cleaning, grading drying, salting, selling and promoting are the key protagonists of Tamil female play in these selected villages. These female have many problems such as lack of support from husbands, family problems (widows, separated, lost husbands during war time), racial marginalization, gender based violence, poor access to bank loans, low returns from dry fish sales. There are many recommendations given from the research findings to the policy makers and the women based organizations for Tamil society to develop a room for women empowerment in the dry fish processing and marketing.
Keywords: Tamil Females; Processing and marketing; Dry fish; Coastal Villages & North Sri Lanka